Diskursus Kurikulum Pendidikan Islam, Konsep dan Implementasinya - Asad Arifin (Faculty of Education and Teacher Training, Islamic State University of Kiai Haji Achmad Siddiq Jember, 2021)
This study aims to discuss the concept of curriculum in an Islamic perspective originating from the interpretation of the verses of the Qur'an and Al-Hadith (Qurdis), their relevance/comparison with curriculum theory in general, and their implications in Islamic education. Using descriptive qualitative methods with literature studies, the researcher concludes that there are many interpretations of the curriculum in the practice of Islamic education, especially in Indonesia so that it has implications for the diversity of Islamic religious-based education systems in Indonesia, ranging from the school system, madrasas to Islamic boarding schools. In the pesantren itself, there are various styles of the education system, such as salaf, modern and a blend of salaf and modern boarding schools.